Management Varicella Using a Family Medicine Approach at the Simpang Keuramat Community Health Center - hr, ufairah (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2024)
Varicella is a contagious infectious disease caused by the Varicella Zoster Virus (VZV). Varicella zoster virus causes transmission between humans through droplets from inhalation and the mouth, and direct contact. Chickenpox causes a skin rash that forms small, itchy blisters that scab over. It usually starts on the chest, back and face and then spreads. The highest prevalence is in the 4 to 10 year age group. Chickenpox has an infection rate of 90%. Secondary cases in household contacts tend to have more severe disease than primary cases. Internal risks include a lack of knowledge about diseases related to their transmission, cleanliness and a weakened immune system. External risks include a lack of family knowledge, and inappropriate family treatment practices before going to the community health center. This paper reports a male patient aged 9 years with the main complaint of reddish spots filled with fluid appearing all over the body. The patient began to experience complaints 4 days ago. The patient's mother said that this was the first time the patient had experienced a complaint like this. The patient had previously sought treatment but not at a health facility and there was no improvement. Various approaches are needed to carry out comprehensive management of health problems in patients. Giving the varicella vaccine is one effort to minimize varicella disease. According to the mother's statement, the patient did not understand her child's illness so she was given education regarding prevention, transmission and treatment.